The nanobots eaudiobook - Nubie, Steve (Twilight Zone Radio Dramas., 2013)
A washed up reporter takes on nanotechnology as his new assignment. He happens across a new way to clean up oceanic oil spills only to find that the microscopic nanobots will eat just about anything—and everything.